Anti-staphylococcus Antibiotics Interfere With the Transcription of Leucocidin ED Gene in Staphylococcus aureus Strain Newman - Yang, Han; Xu, Su; Huang, Kaifeng; Xu, Xiaogang; Hu, Fupin; He, Chunyan; Shu, Wen; Wang, Zhiyan; Gong, Fang; Zhang, Chuanling; Liu, Qingzhong (Frontiers in Microbiology, 2020)
Antibiotics have been described to modulate bacterial virulence gene expression. This study aimed to assess the changes caused by anti-Staphylococcus agents in the transcription of leucocidin ED gene (lukED) of S. aureus strain Newman in vitro and in vivo, and to determine whether the altered expression is agr-dependent. The bacteria were exposed to subinhibitory concentrations (1/2, 1/4, or 1/8 MIC) of 11 antibiotics, and the expression of lukE and agr-effector RNAIII were determined using qRT-PCR. In vivo experiments were performed to evaluate the impact exerted by 6 representative antibiotics on the transcription of both genes. Molecular analysis showed that in vitro lukE transcription was dramatically promoted in the Newman strain exposed to sub-MICs of vancomycin, trimethoprim-sulfamethoxazole, clindamycin, gentamicin, daptomycin, and ciprofloxacin, and considerably reduced when stimulated by cefazolin, erythromycin, rifampicin, tigecycline, and linezolid. In the murine abscess model, tigecycline significantly decreased the transcription of lukE and the bacterial numbers, while vancomycin increased them; although cefazolin increased the lukE expression (contrary to the in vitro effect), it had a remarkable role in reducing bacterial load. The correspondence analysis shows that RNAIII expression varied under 7 of 11 antibiotics in vitro and 6 drugs in vivo were consistent with lukE transcripts. In conclusion, our data show that anti-Staphylococcus antibiotics exert modulatory effects on lukE expression in vitro and/or in vivo, and the changed expression caused by some drugs may be involved with agr activity, thus providing a guide to choose appropriate agents to avoid promoting bacterial virulence in lukED-positive S. aureus infections.